2010
DOI: 10.1103/physrevb.82.195114
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of pristine and K-doped solid picene: Nonrigid band change and its implication for electron-intramolecular-vibration interaction

Abstract: We use photoemission spectroscopy to study electronic structures of pristine and K-doped solid picene. The valence band spectrum of pristine picene consists of three main features with no state at the Fermi level ͑E F ͒ while that of K-doped picene has three structures similar to those of pristine picene with new states near E F , consistent with the semiconductor-metal transition. The K-induced change cannot be explained with a simple rigid-band model of pristine picene but can be interpreted by molecular-orb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
35
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 26 publications
(44 reference statements)
9
35
3
Order By: Relevance
“…Figure 1 the spectrum reported by Okazaki et al [23] for x = 1, while for larger doping concentration it clearly moves away from µ exp , leaving a (half)gap of ≈ 0.5 eV. However, the near-Fermi level position of F 1 around x = 1 should not be mistaken for a metallic Fermi edge.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Figure 1 the spectrum reported by Okazaki et al [23] for x = 1, while for larger doping concentration it clearly moves away from µ exp , leaving a (half)gap of ≈ 0.5 eV. However, the near-Fermi level position of F 1 around x = 1 should not be mistaken for a metallic Fermi edge.…”
mentioning
confidence: 91%
“…In fact, the importance of electron-electron correlations in K 3 picene was pointed out by Giovannetti et al [21] and Kim et al [22] who found an insulating state with antiferromagnetic order from ab initio calculations. Experimentally, the picture of the electronic structure has remained controversial: while one photoemission study reported the appearance of metallic spectral weight at the Fermi level for x = 1 [23], other authors [24,25] failed to observe a metallic Fermi edge for a wide concentration range from x = 0.22 to 3.6 and speculated about the possible role of correlations and polaronic effects [24].…”
mentioning
confidence: 99%
“…15 In K 3 picene, the six additional electrons from potassium atoms occupy the lowest four overlapping π * bands and the system becomes metallic. 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Besides the theoretical works, experiments on the electronic structure of K-doped and undoped picene have also been performed by using electron spectroscopies. [7][8][9][10][11] These experimental works show the formation of new electronic states near E F upon K doping. However, detailed characteristics of doping-induced electronic states in K-doped picene have not yet been clarified due to the lack of element/site selectivity in the earlier experiments.…”
Section: Introductionmentioning
confidence: 98%